2001
DOI: 10.1177/000348940111001103
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Anterior Glottic Restenosis in a Canine Model with Topical Mitomycin-C

Abstract: To develop a model for recurrent anterior glottic stenosis and to test the efficacy of topical mitomycin-C in preventing restenosis, we induced anterior glottic stenosis with a CO2 laser in 5 dogs. In 3 dogs, recurrence was established after surgical lysis. Subsequently, the 3 dogs received a single topical 3-minute treatment with a 1% solution of mitomycin-C after a second surgical lysis. In a parallel experiment, the other 2 dogs received a single topical 3-minute treatment with a 1% solution of mitomycin-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 20 publications
3
42
0
1
Order By: Relevance
“…[8][9][10] The concentration used in this study was less than the 10 mg/mL of MMC concentration reported by Spector et al 7 but is comparable to the concentrations used clinically. The safe use of MMC is also supported by a recent report showing that the use of MMC at concentrations in excess of 0.4 mg/mL did not alter the protein concentrations in the extracellular matrix or the apoptosis rate.…”
Section: Commentsupporting
confidence: 49%
See 4 more Smart Citations
“…[8][9][10] The concentration used in this study was less than the 10 mg/mL of MMC concentration reported by Spector et al 7 but is comparable to the concentrations used clinically. The safe use of MMC is also supported by a recent report showing that the use of MMC at concentrations in excess of 0.4 mg/mL did not alter the protein concentrations in the extracellular matrix or the apoptosis rate.…”
Section: Commentsupporting
confidence: 49%
“…9,10 In a previous experiment, MMC was used only to prevent recurrence after the lysis of anterior glottic webs that were originally induced by laser injury of the vocal folds. 7 These clinical and experimental studies of MMC suggest that MMC can be used for prevention of AGS following microsurgical removal of lesions involving both anterior vocal folds. However, to our knowledge, there have been no reports of experiments in which MMC was applied at the time of initial surgery to prevent the development of AGS.…”
Section: Nterior Glottic Stenosismentioning
confidence: 98%
See 3 more Smart Citations